Understanding research in second language learning : A teacher's guide to statistics and research design - Brown, James Dean (Cambridge University Press, 1988)
This text focuses on the skills and processes necessary for understanding statistical research in language learning. Brown explains the basic terms of statistics, the structure and organization of statistical research reports, the system of statistical logic, and how to decipher tables, charts, and graphs.